Flow And Heat Transfer Along A Permeable Stretching/Shrinking Curved Surface In A Hybrid Nanofluid - Pop, Ioan Mihai; Waini, Iskandar; Ishak, Anuar (Institute of Physics Publishing, 2019)
The problem of the unsteady hybrid nanofluid flow and heat transfer along a stretching/shrinking curved surface with mass suction is studied. By using the similarity transformation, the partial differential equations are transformed into a set of ordinary differential equations. The transformed equations are then solved numerically using the boundary value problem solver (bvp4c) in Matlab software. The effects of several parameters on the skin friction coefficient and the local Nusselt number as well as the velocity and temperature profiles are presented and discussed. It is found that dual solutions exist for a certain range of the stretching/shrinking, suction and curvature parameters. The critical values of these parameters decrease with the increasing of the copper (Cu) nanoparticle volume fractions. A temporal stability analysis is performed to determine the stability of the dual solutions over the long run, and it is reveals that only one of them is stable while the other is unstable.